2019
DOI: 10.1063/1.5125468
|View full text |Cite
|
Sign up to set email alerts
|

Jeffery orbits in shear-thinning fluids

Abstract: We investigate the dynamics of a prolate spheroid in a shear flow of a shear-thinning Carreau fluid. The motion of a prolate particle is developed analytically for asymptotically weak shear thinning and then integrated numerically. We find that shear-thinning rheology does not lift the degeneracy of Jeffery orbits observed in Newtonian fluids but the instantaneous rate of rotation and trajectories of the orbits are modified. Qualitatively, shear thinning has a similar effect to elongating the particle in a New… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 49 publications
7
19
0
Order By: Relevance
“…The rotation of an axisymmetric inertia-free spheroidal particle in the simple shear flow was described by Jeffery . It was shown that, in addition to rotation with the local angular velocity of the flow, the particle also has a rotational component that depends on its aspect ratio and orientation as the particle unequally experiences the surrounding velocity field. , Furthermore, as shown by Hinch and Leal, aberrations from the axisymmetric geometry lead to large changes in particle rotation.…”
Section: Resultsmentioning
confidence: 99%
“…The rotation of an axisymmetric inertia-free spheroidal particle in the simple shear flow was described by Jeffery . It was shown that, in addition to rotation with the local angular velocity of the flow, the particle also has a rotational component that depends on its aspect ratio and orientation as the particle unequally experiences the surrounding velocity field. , Furthermore, as shown by Hinch and Leal, aberrations from the axisymmetric geometry lead to large changes in particle rotation.…”
Section: Resultsmentioning
confidence: 99%
“…Rod-like particles rotate even in laminar ow, and during the rotation, they can buckle. [50][51][52][53][54] This buckling causes poor alignment of rod particles, and yields a macroscopic assembly that has an undensied structure. 20 This buckling behavior is controlled by the interplay of the elastic bending force and shear stresses.…”
Section: Aligning the Cnt Bundles In The Shear Owmentioning
confidence: 99%
“…For the particle in weakly shear-thinning fluids, the asymptotic analysis has been utilized to obtain the asymptotic solution of the non-Newtonian flow surrounding particles (Datt et al. 2015; Elfring 2017; Abtahi & Elfring 2019; van Gogh et al. 2022).…”
Section: Introductionmentioning
confidence: 99%
“…2022). Based on the reciprocal theorem and perturbation expansion, Abtahi & Elfring (2019) proposed an analytical torque model for an inertialess prolate particle immersed in a Stokesian shear flow of a Carreau-type fluid. Their model demonstrates that the particle in weak shear-thinning fluids retains the degeneracy of Jeffery orbits in Newtonian fluids, and the particle rotation rate is slightly attenuated by shear-thinning rheology.…”
Section: Introductionmentioning
confidence: 99%